TEACHER-STUDENT INTERACTION IN THE ENGLISH CLASSROOM AT SECOND YEAR OF SMP MUHAMMADIYAH 10 SURAKARTA IN 2006 / 2007 ACADEMIC YEAR - HASANAH SR , USWATUN (2007)
This research is conducted to achieve some objectives, 1) to describe the process of classroom interaction between teacher and students in the English class for second year students of SMP Muhammadiyah 10 of Surakarta in the term of turn-allocation and turn -taking behavior of the language teaching and learning process, 2) to describe what kinds of problems occur in the classroom interaction involving the teacher and the students. The method used in this study is descriptive method. The research was conducted on Februa ry, 2007. The subject of the study is the second year students of SMP Muhammadiyah 10 Surakarta. In this research, the writer uses an interactive model of analysis that includes three main components, namely the reduction of data, display of data, and conc lusion or verification. The result of the study shows that the interaction was dominated by the teacher during the lesson. The teacher-students interaction (turn allocation and turn taking behaviour) run unbalanced. Only a small part of the classroom interaction is filled in with students talk. They did not play an active role in building a good communication with their teacher. As the result, the classroom activity seemed to be monologue not dialogue. It means the activity run from one side only, that is from the teacher. In this condition, teaching and learning activity is not in the form of 'take and give' but 'give and give'. This problem is influenced by many factors; it can be from teacher, student, or material. In the research, the writer also finds there are many factors influenced the quality of interaction and it can become problems of interaction. They are: 1) the student under confident and did not want to take a risk, 2) the student has problem in vocabulary mastery, 3) the student has below standard resources, 4) the student do not have strong motivation, 5) the teacher does not give enough opportunity to the student, 6) the teacher overestimates the students' competence, 7) technique used by the teacher, 8) the problems related to the material, 8) only one English teacher in the institution.